AI‑driven interactive educational avatars for smart education - Mandic, Danimir; Miscevic , Gordana; Dzinovic, Milanka (Sociološki pregled, 2025)
The paper explores the use of interactive educational avatars powered by artificial intelligence within smart education initiatives in Serbia. It analyzes the attitudes of 173 teachers from all levels of education, based on informal training. The results show strong positive correlations between acquired experiences and the acceptance of avatars, particularly those featuring two-way communication and adaptive content. The study highlights advanced engineering features such as machine learning, natural language processing, and emotion analysis. It also addresses real-time adaptability, data privacy, and ethical issues. The role of institutions such as CRAIE is emphasized, with a focus on professional development and interdisciplinary collaboration for the effective integration of avatars in the field of education.